(untitled) (Fiep Bulletin - online, 2014)
This research aimed at investigating the perception of students of a public school in Teresina/PI about the theoretical and practical lessons of physical education offered to them. The method used was the descriptive and exploratory, with a qualitative approach. A field survey was conducted through the application of a questionnaire containing open and closed-ended questions. 100 students of both sexes were surveyed, being 48 girls and 52 boys, all enrolled in the 8th and 9th grades of Primary School in the above mentioned school. The data were collected on October 21- 22, 2010. The results have shown that most students accept explanatory lessons of physical education and that they have revealed the desire to learn more about soccer and indoor soccer in the practical lessons. In conclusion, it could be said that theoretical lessons in consonance with practical lessons, according to the students surveyed, is the best way to teach physical education.